2003
DOI: 10.1038/ng1268
|View full text |Cite
|
Sign up to set email alerts
|

A putative RUNX1 binding site variant between SLC9A3R1 and NAT9 is associated with susceptibility to psoriasis

Abstract: Psoriasis (OMIM 177900) is a chronic inflammatory skin disorder of unknown pathogenesis affecting approximately 2% of the Western population. It occurs more frequently in individuals with human immunodeficiency virus, and 20-30% of individuals with psoriasis have psoriatic arthritis. Psoriasis is associated with HLA class I alleles, and previous linkage analysis by our group identified a second psoriasis locus at 17q24-q25 (PSORS2; ref. 7). Linkage to this locus was confirmed with independent family sets. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
210
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(220 citation statements)
references
References 27 publications
8
210
0
2
Order By: Relevance
“…The slc2f2 (rs3792876) SNP was selected as the most likely functional mutation because polymorphism was predicted to affect binding of a transcription factor, RUNX-1. Several recent reports have suggested that RUNX-1 binding-site polymorphisms may be associated with a number of autoimmune diseases (3,4). There is no doubt that the functional data provide support that the putative RUNX-1 binding site does indeed affect RUNX-1 binding.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…The slc2f2 (rs3792876) SNP was selected as the most likely functional mutation because polymorphism was predicted to affect binding of a transcription factor, RUNX-1. Several recent reports have suggested that RUNX-1 binding-site polymorphisms may be associated with a number of autoimmune diseases (3,4). There is no doubt that the functional data provide support that the putative RUNX-1 binding site does indeed affect RUNX-1 binding.…”
mentioning
confidence: 73%
“…Studies of an intron 1 SNP in linkage disequilibrium (LD) with it showed that the polymorphism affected binding of a transcription regulator, RUNX-1. This was, therefore, thought to be the disease-causing variant, particularly in light of several other recent publications showing that polymorphisms affecting RUNX-1 binding sites may be associated with a variety of autoimmune diseases (3,4).…”
mentioning
confidence: 99%
“…13 This suggests that regulation of cytokine production might be influenced by other genes, for example, a regulatory single-nucleotide polymorphism (rSNP). 14,15 The unknown regulatory genes may be localized with linkage analysis, but, to our knowledge, linkage studies of cytokine production capacity have not been reported. Even the heritability of variation in cytokine production is largely unknown.…”
mentioning
confidence: 99%
“…Although sequencing of Cw6 has shown an association between alanine at position 73 and psoriasis in Japanese patients, this was not been confirmed in patients of European extraction. Recently, gene mutations have been reported in regions containing SLC9ARI on the 17q25 locus (Helms et al 2003) and SLC12A8 on the 3q locus (Hewett et al 2002). SLC9ARI is concerned with transport of ions across cell membranes and immune synapse formation in T cells and is adjacent to a putative binding site for the transcription factor RUNXI.…”
Section: Chromosome Loci and Genesmentioning
confidence: 99%